Batman, the complete animated series [videorecording (DVD)] - Timm, Bruce; Radomski, Eric; Conroy, Kevin; Zimbalist, Efrem, Jr., 1918-2014; Hastings, Bob, 1925-2014; Barbeau, Adrienne, 1945-; Hamill, Mark (Warner Home Video, 2004)
"When the two shots rang out, Bruce Wayne's life changed forever. He pledged himself to justice, and he held that oath for years. Wearing many names--the Dark Knight, the World's Greatest Detective, the Caped Crusader, and Gotham's Greatest Hero--he battled tragic foes like the Joker, Penguin, Mr. Freeze and so many more. But deep inside, he knew that he shared something with them that most of humanity wouldn't understand--a commitment to the fight ..."--Back cover